Harnessing The Power of Artificial Intelligence in Dermatology: A Paradigm Shift in Patient Care - Choudhary, Dilip (Birat Journal of Health Sciences, 2024)
The field of dermatology is undergoing a transformative revolution with the integration of artificial intelligence (AI) technologies. From enhancing diagnostic accuracy to personalized treatment recommendations, AI is reshaping the way skin conditions are evaluated and managed. This editorial explores the potential impact of AI in dermatology and highlights the opportunities and challenges associated with its adoption.